The Influence of Value-Chain Governance on Innovation Performance: A Study of Italian Suppliers - Emanuele Brancati; Carlo Pietrobelli; Caio Torres Mazzi (Institute of Labor Economics (IZA), 2021)
This paper explores how value-chain governance affects the innovation performance of suppliers of intermediate products. We take advantage of a unique dataset of Italian firms to identify governance regimes along suppliers' technological capabilities and the level of explicit coordination in the value chain. Our results indicate that `modular' value-chain governance is more conducive to innovation for suppliers, especially when these firms have medium capability levels. Conversely, market-based governance modes appear to strongly reduce the innovativeness of suppliers with low capability. These patterns are also reflected in export performances and sales of innovative products. Our results go partially against other findings in the GVC literature, whereby relational value chains are seen to provide the most favorable environment to learn and innovate. Interestingly, the highest levels of technological capabilities consistently reduce the correlation between supplying intermediates and innovation performance, which indicates that technology-gap is an important mediator of learning within value chains.
Keywords: F14; O30; 330; global value chains; export; suppliers; innovation; technological capabilities